The mismeasure of education - Horn, Jim; Wilburn, Denise (Emerald Publishing Limited : IAP, Information Age Publishing, Inc., 2013)
With new student assessments and teacher evaluation schemes in the planning or early implementation phases, this book takes a step back to examine the ideological and historical grounding, potential benefits, scholarly evidence, and ethical basis for the new generation of test based accountability measures. After providing the political and cultural contexts for the rise of the testing accountability movement in the 1960s that culminated almost forty years later in No Child Left Behind and Race to the Top, this book then moves on to provide a policy history and social policy analysis of value-added testing in Tennessee that is framed around questions of power relations, winners, and losers.In examining the issues and exercise of power that are sustained in the long-standing policy of standardized testing in schools, this work provides a big picture perspective on assessment practices over time in the U. S.; by examining the rise of value-added assessment in Tennessee, a fine-grained and contemporary case is provided within that larger context. The last half of the book provides a detailed survey of the research based critiques of value-added methodology, while detailing an aggressive marketing campaign to make value-added modeling (VAM) a central component of reform strategies following NCLB. The last chapter and epilogue place the continuation of test-based accountability practices within the context of an emerging pushback against privatization, high stakes testing, and other education reforms.This book will be useful to a wide audience, including teachers, parents, school leaders, policymakers, researchers, and students of educational history, policy, and politics.